The best practices of STEM education for children aged 5-6 years old - Muhammad Nur Azam Ghazali (2022)
The purpose of this study is to determine how STEM education can bridge the gap between the productivity of early childhood educators and government policies in elevating the quality of education based on 21st century learning in Malaysia. There are 4 objectives of this study which are (i) explore the best practice in Early Science towards the implementation of STEM activity in kindergarten; (ii) explore the best practice in Early Mathematics towards the implementation of STEM activity in kindergarten; (iii) explore technology-assisted teaching tools towards the implementation of STEM activity in kindergarten; and (iv) explore engineering activity towards the implementation of STEM activity in kindergarten. The method of exploratory case study was used to design this study, which was based on a qualitative study. It was successfully carried out at three different private kindergartens in Malaysia, with four kindergarten teachers and 39 kindergarten students participating. They were selected using the purposive sampling technique. The data of the study were obtained through the results of data triangulation using three research instruments which are interviews, observations, and document analysis. The data of this study were analysed inductively using thematic analysis using ATLAS ti.8. According to the findings, there are eight best practises of STEM education based on the teacher's teaching and learning session. The study's implications revealed that teachers' initiative in providing STEM activities to children is a benchmark for the improvement of STEM education in Malaysia. The most significant contribution of this study is that it can bridge the gap between the Ministry of Education Malaysia's aspirations for elevating STEM education at the global level. If teachers are able to provide effective activities to children by implementing best teaching practices, it will result in children who will continue to explore such STEM activities for the sake of their future and nation.